EDINA Digimap: New Developments in the Internet Mapping and Data Service for the UK Higher Education Community - Morris, Barbara; Medyckyj-Scott, David; Burnhill, Peter (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
Following successful trials in six United Kingdom university map collections, the EDINA Digimap web-based mapping service was launched on 10 January 2000. Digimap gives access to current Ordnance Survey of Great Britain (OS) maps ranging in scale from 1:1,250 to 1:250,000 and also to the raw digital map data. This paper looks at the background to the service, the facilities it offers to the UK Higher Education (HE) community, and future plans for incorporating other data, including historic mapping and aerial photography.